St. Augustinegrass for Florida Lawns - Laurie E. Trenholm; John L. Cisar; J. Bryan Unruh (EDIS)
Revised! ENH-5, a 12-page illustrated fact sheet by L.E. Trenholm, J.L. Cisar, and J. Bryan Unruh, provides Florida homeowners with the information necessary for the selection and maintenance of St. Augustingrass lawns, including descriptions of available cultivars and tables for growth characteristics, recommended fertility rates, and fertilization calendar. This version includes new illustrations and updated recommendations throughout. Published by the UF Department of Environmental Horticulture, June 2006.